The Effect of Giving Bokashi Fertilizers with Different Compositions on the Growth of Tubifex sp. With a multilevel recirculation system - Saperizal Agus Suandi; Iskandar Putra; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT                The research of  Effect of Giving Bokashi Fertilizers with Different Compositions on the Growth of Tubifex sp. With a multilevel recirculation systemhas been implemented  in 38 Kamboja street, Simpang Baru, Panam, Pekanbaru, Riau from October 2017 until Jauary 2018. The method used is an experimental method with four treatments consisting of bokashi fertilizer from chicken manure, bokashi fertilizer from cow  manure, bokashi fertilizer from quail manure, and  bokashi fertilizer from buffalo manure. Each treatment was repeated three times. The data observed is the growth of biomass weight, average length, and water quality. The results of this study with the treatment of  Effect of Giving Bokashi Fertilizers with Different Compositions very significant influence (P<0,05) on the growth of biomass weight of silk worms. Biomass is highest in treatment P1(bokashi fertilizer from chicken manure)  in 32,67 g.  As for the average length, The results of this study with the treatment of  Effect of Giving Bokashi Fertilizers with Different Compositions very significant influence (P<0,05) on the average length, The average length of the highest in treatment P1 (2,90 cm). Water quality measured during the study was the temperature (26-29˚C), pH (6-7), dissolved oxygen (6,0-6,5 ppm),and water discharge (0,05 L/Sec-0,12 L/Sec). From this study it can be concluded that giving Bokashi Fertilizers with Different Compositions can effect the growth of silk worms.  Key Word: Tubifex sp, Bokashi Fertilizer, Chicken manure, Quail Manure, Cow Manure, Buffalo Manure, Biomass, dan Average length